The effect of dynamic loading on bacterial microleakage of the dental implant fixture-abutment interface: An in vitro study - Mehrak Amjadi (Wolters Kluwer Medknow Publications, 2021)
Aim: Bacterial micro leakage at implant-abutment interface under functional loading is an important factor, may lead to crestal bone loss and affect the long term success of dental implants. Due to the limited studies about the implant systems with a connection of Slip joint design, this study aimed to evaluate the effect of dynamic loading on bacterial leakage at the implant-abutment interface with slip joint connection. Settings and Design: In vitro- comparative study. Materials and Methods: A total of 20 implants and abutments with slip joint connections (Tapered Screw-Vent, 3.7 mm ×10 mm, Zimmer Dental, USA) was examined and depends on using functional loading were divided into two groups; loaded and unloaded. Initially, 10 μl of Brain Heart Infusion (BHI) culture broth was pipetted to the internal lumen of each implant, then the abutments were tightened to the fixtures and crowns were cemented. In the unloaded group, samples were immersed in E-Coli suspension for 5 days. In the loaded group, samples were immersed in microbial suspension under 500000 cycles using a cyclic load device. Following disconnection of fixtures and abutments, microbial samples were taken from the internal lumen of implants and colonies were counted. Data were analyzed using. Statistical Analysis Used: Mann-Whitney statistical test, SPSS version 24. Results: The mean rate of micro leakage in unloaded and loaded groups was 4000 CFU/ml and 27000 ± 31640 CFU/ml respectively. Bacterial colonies grew in 10% of unloaded samples and 50% of loaded samples. This difference was statistically significant. (P < 0.05) Conclusions: Microbial micro leakage at the implant-abutment interface with slip joint design increased significantly after functional loading.